TRANSIENT, SYNOBDUCTION EXHUMATION OF ZAGROS BLUESCHISTS INFERRED FROM P-T, DEFORMATION, TIME, AND KINEMATIC CONSTRAINTS: IMPLICATIONS FOR NEOTETHYAN WEDGE DYNAMICS - Agard P.; Gerber W.; Omrani J.; Meyer B.; Labrousse L.; Vrielynck B.; Jolivet L.; Yamato P.; Monié P.; Molinaro M. (My University, 2006)
We present the first P-T, deformation time, and kinematic constraints on the only known blueschist facies rocks (BS) present in the Zagros (Hajiabad area). The BS were underplated below the Sanandaj-Sirjan zone and crop out as kilometer-scale bodies within extensive colored melange units marking discontinuously the Neotethyan suture zone. P-T estimates point to high-pressure/low-temperature (HP-LT) conditions around 11 kbar and 520-530°C for the majority of BS, along a ~15°C km-1 gradient. Some exotic blocks in matrix serpentinite reached 17-18 kbar at ~500°C. In situ laser probe 40Ar-39 Ar radiometric age constraints on phengite cluster between 85 and 95 Ma and suggest that (1) synponvergence exhumation of Zagros BS from 35-50 km to depths <15-20 km was accomplished before 80 ma, (2) bs exhumation corresponded to a transient process with respect the long-lived subduction beneath iran (~150-35 ma), and (3) age constraints for zagros are 5-10 myr older than nearby oman hp-lt rocks broadly coincide obduction processes in region (circa 95-70 ma). we propose that mechanical coupling across neotethyan zone (nsz) modified by large-scale plate rearrangement accompanying obduction, allowing short-lived of bs. ceased at end when arabian continental margin stopped. kinematic calculations suggest convergence velocities nsz likely doubled (to ~5-6 cm yr-1) during the period 118-85 Ma, so that BS exhumation may have been promoted by a combination of obduction movements and increased convergence velocities. Copyright 2006 by the American Geophysical Union.